Augustine's Resurrection Framework: Clarifying and Connecting Senses of "Resurrection" - McGlothlin, Thomas D. (Augustinian studies, 2024)
Augustine combined two distinctions to develop an elegant interpretive framework for embracing multiple senses of "resurrection," resolving tensions that had bedeviled predecessors such as Irenaeus and Tertullian. The first distinction was between the general resurrection of the body and an accompanying bodily transformation restricted to the saved. The second distinction, which he shared with many fourth-century authors but may have drawn most directly from Tyconius, was between a "first," spiritual resurrection experienced now by the baptized and a "second," bodily resurrection experienced eschatologically by all. Scholars have noted both distinctions separately but not explored how Augustine came to adopt them and use them in combination. Augustine deployed these distinctions together to resolve theological problems caused by apparent Pauline connections between the "first" resurrection of believers and the "second" resurrection of all.